Portugal como um HUB para o transporte marítimo de contentores - Vieira, Ana Raquel Serra Silva (2020)
The main objective of this study is to understand how container shipping from the Port of Sines, the main Portuguese port and also from the Iberian Peninsula, can become a HUB port. The adopted methodology is of qualitative nature, having been proceeded to the documentary analysis. The results indicate that the Port of Sines can and should become a HUB port. It is concluded that the Port of Sines, in addition to having several benefits at its disposal, has the potential to become a HUB port, due to its own characteristics and its strategic location, namely, an LNG HUB. In addition to continuing to handle large quantities of containerized cargo, the Port of Sines is preparing to increase its competitiveness and assert itself in commerce and shipping by expanding one of its terminals (Terminal XXI) and the creation of the Vasco da Gamma. Through these projects, the Port of Sines will be able to move more cargo, accommodate the largest ships in the world and respond to business opportunities with other countries, namely with China (through the Belt and Road) and with the USA (through the expansion of the Port of Sines and the new Terminals).